Peran Pembelajaran Musik Gambus dalam Menumbuhkan Apresiasi terhadap Tradisi Lisan Melayu Riau di Perguruan Tinggi - Laila Fitriah; Djulian Anggara; Tengku Ritawati; Nike Suryani (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the role of Gambus music education in fostering appreciation for Riau Malay oral traditions in higher education. Amidst the wave of globalization, oral traditions such as pantun, syair, and gurindam are losing their space of actualization among the younger generation. This research employs a descriptive qualitative approach with a case study design at the Universitas Islam Riau. Data were collected through participant observation, in-depth interviews, and documentation. The results indicate that Gambus music learning, which integrates experiential learning methods through three main stages textual analysis, musical practice, and contextual reflection is effective in increasing students' cultural awareness. The integration of oral tradition texts into musical materials allows students to deeply internalize moral, religious, and social values. Despite challenges such as limited curriculum time allocation, the involvement of expert practitioners serves as a key supporting factor in providing an authentic learning experience. The study concludes that Gambus music in higher education functions as a strategic educational instrument to revitalize oral traditions as a